Colonisation with pathogenic drug-resistant bacteria and Clostridioides difficile among residents of residential care facilities in Cape Town, South Africa - September, Jason (Department of Medicine, 2020)
Objectives Residential care facilities (RCFs) act as reservoirs for multidrug-resistant organisms (MDRO). There are scarce data on colonisation with MDROs in Africa. We aimed to determine the prevalence of MDROs and C. difficile and risk factors for carriage amongst residents of RCFs in Cape Town, South Africa. Methods We performed a cross-sectional surveillance study at three RCFs. Chromogenic agar was used to screen skin swabs for methicillin-resistant Staphylococcus aureus (MRSA) and stool samples for extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-E). Antigen testing and PCR was used to detect Clostridiodes difficile. Risk factors for colonisation were determined with logistic regression. Results One hundred fifty-four residents were enrolled, providing 119 stool samples and 152 sets of skin swabs. Twenty-seven (22.7%) stool samples were positive for ESBL-E, and 13 (8.6%) residents had at least one skin swab positive for MRSA. Two (1.6%) stool samples tested positive for C. difficile. Poor functional status (OR 1.3 (95% CI, 1.0 – 1.6)) and incontinence (OR 2.9 (95% CI, 1.2 – 6.9)) were significant predictors for ESBL-E colonisation. There was a trend towards higher MRSA colonisation in frail care areas. Conclusion There was high prevalence of colonisation with MDROs but low C. difficile carriage, with implications for antibiotic prescribing and infection control practice.